Food safety benchmarking between retail outlets in Greece. Issue 7 (1st October 2018) - Souliotis, Andreas; Giazitzi, Katerina; Boskou, George
Abstract : Purpose: The purpose of this paper is to develop and implement methods for benchmarking the food safety and hygiene between retail outlets at the same time or at the same retail outlets at different times. Design/methodology/approach: A tailor made questionnaire for the collection of food safety and hygiene remarks was designed to be applied in a large chain of retail outlets. The remarks were classified in the five categories of the Ishikawa model (materials, methods, personnel, equipment and environment). The retail outlets were located all over Greece and the audits were performed in a one-year term. Food safety experts were used as auditors after a six-month training period. The data collected were subject to analysis of the benchmarking scores and to cluster analysis to identify regions with similar food safety profiles. Findings: Polar charts were used to illustrate the benchmarking scores for each of the five categories of evaluation per auditing period at the retail outlets. Another polar chart illustrates the benchmarking scores for each of the 12 regions of Greece. Cluster analysis demonstrates that some regions, like Ionian Islands and South Aegean, have similar profiles on food safety for the retail outlets. Originality/value: The developed methodology can be used by retail companies with several outlets or by a group or an association of companies in order to identify problematic sectors and to set priorities while dealing with issues of food safety and hygiene. The work is limited to the Greek outlets but the methodology has potential application to every other country.